2006
DOI: 10.1530/eje.1.02183
|View full text |Cite
|
Sign up to set email alerts
|

Primary hypophysitis: clinical-pathological correlations

Abstract: Objective: Primary hypophysitis comprises of three distinct histomorphological entities: lymphocytic, granulomatous and xanthomatous. Clinical features of the three subtypes for diagnostic and treatment strategies have yet not been well characterized. Methods: Endocrine function, visual fields and acuity as well as magnetic resonance imaging characteristics were assessed before and after transphenoidal surgery in the largest series of 31 patients with primary hypophysitis (21 lymphocytic, 6 granulomatous, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
169
4
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(194 citation statements)
references
References 27 publications
16
169
4
4
Order By: Relevance
“…17 MR imaging features more indicative of AH include a symmetric enlargement of the pituitary gland, a thickened nontapering pituitary stalk, and an intact sellar floor. 18,19 In contrast, pituitary macroadenomas are frequently asymmetric, often displacing the infundibulum, and rarely involve the stalk or erode the sellar floor. 20 In addition, macroadenomas appear heterogeneous both before and after contrast medium administration, in direct relationship to their size, though heterogeneity can also occur in AH.…”
mentioning
confidence: 99%
“…17 MR imaging features more indicative of AH include a symmetric enlargement of the pituitary gland, a thickened nontapering pituitary stalk, and an intact sellar floor. 18,19 In contrast, pituitary macroadenomas are frequently asymmetric, often displacing the infundibulum, and rarely involve the stalk or erode the sellar floor. 20 In addition, macroadenomas appear heterogeneous both before and after contrast medium administration, in direct relationship to their size, though heterogeneity can also occur in AH.…”
mentioning
confidence: 99%
“…Glucocorticoid therapy has been advocated to reduce inflammation and has been temporarily effective in some patients with primary hypophysitis. However, Gutenberg et al (2006) demonstrated that methylprednisolone therapy, administered to one of four patients with XH, did not yield an efficient outcome. Steroid therapy seems to be less effective in XH compared to other kinds of primary hypophysitis…”
Section: The Patient Requires Gc Supplementation Only In Case Of Recumentioning
confidence: 97%
“…Maternal mortality during labor is reported in a case (235). The striking temporal association of pregnancy and LyH is not clarified yet, but there are possible explanations, which are as follows: i) pregnancy may unmask a latent pituitary insufficiency and lactotroph hyperplasia may contribute to compression signs caused by LyH, both resulting in earlier diagnosis during gestation (236,237). ii) The increased size of pituitary gland, which may lead to the release of pituitary antigens, may be one of the reasons for autoimmune hypophysitis.…”
Section: Lymphocytic Hypophysitismentioning
confidence: 99%
“…Several causes have been suggested for hyperprolactinemia: stalk compression or the inflammatory process itself altering the inhibitory effect of dopamine on PRL or the release of hormones into the bloodstream from destructed tissue or PRL-stimulating antibodies (243)(244)(245). Hypoprolactinemia manifested by the inability to lactate after pregnancy may also be seen with LyH (186,237,246).…”
Section: Lymphocytic Hypophysitismentioning
confidence: 99%
See 1 more Smart Citation